Simulation modeling of the phase behavior of palm oil-supercritical carbon dioxide - Lim, Chee Siang; Abd. Manan, Zainuddin; Sarmidi, Mohamad Roji (Springer Berlin / Heidelberg, 2003)
The phase behavior of crude palm oil (CPO) with supercritical CO2 was successfully modeled in an Aspen PlusÂ® 10.2.1 commercial simulator (Aspen Technology Inc., Cambridge, MA) using the Redlich-Kwong-Aspen (RKA) equation of state thermodynamic model. The modeling procedure involved estimating pure component vapor pressures and critical properties and computing a regression of phase equilibrium behavior. The interaction parameters for the RKA model were obtained from the regression of experimental phase equilibrium data for a binary system of palm oil components-supercritical CO2 available in the literature. The distribution coefficients and solubilities of palm oil components obtained from this simulation showed good agreement with experimental data obtained from the literature. The model provides an efficient and cost-effective alternative for the preliminary design and optimization of a supercritical fluid extraction process involving a complex CPO-supercritical CO2 system.